2007
DOI: 10.1103/physrevb.75.184111
|View full text |Cite
|
Sign up to set email alerts
|

Annealing twins in nanocrystalline fcc metals: A molecular dynamics simulation

Abstract: We report fully three-dimensional atomistic molecular dynamics studies of grain growth kinetics in nanocrystalline Cu of 5 nm average grain size. We observe the formation of annealing twins as part of the grain growth process. The grain size and energy evolution was monitored as a function of time for various temperatures, yielding an activation energy for the process. The atomistic mechanism of annealing twin formation from the moving boundaries is described. DOI: 10.1103/PhysRevB.75.184111 PACS number͑s͒: 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…Farkas et al [124] reported three-dimensional simulations of grain growth beginning with 5 nm grain sizes and were able to generate larger grains and possibly more realistic distributions while also obtaining the activation energy for annealing twins and grain boundary motion. Figure 22 shows 26 fivefold twin formation during an annealing simulation of nanocrystalline Cu as directly compared to experimental evidence of such star shaped twins in nanocrystalline NiW [125] as well as earlier studies by Zhu et al [126] that found fivefold twins formed in nanocrystalline Cu by high-pressure torsion.…”
Section: Interatomic Potentialsmentioning
confidence: 98%
“…Farkas et al [124] reported three-dimensional simulations of grain growth beginning with 5 nm grain sizes and were able to generate larger grains and possibly more realistic distributions while also obtaining the activation energy for annealing twins and grain boundary motion. Figure 22 shows 26 fivefold twin formation during an annealing simulation of nanocrystalline Cu as directly compared to experimental evidence of such star shaped twins in nanocrystalline NiW [125] as well as earlier studies by Zhu et al [126] that found fivefold twins formed in nanocrystalline Cu by high-pressure torsion.…”
Section: Interatomic Potentialsmentioning
confidence: 98%
“…The specimen final state that is used in computations by the method of molecular statics at 0 K is attained by annealing at 300 K with the molecular dynamics method which is followed by cooling to 0 K. It is supposed that model NC specimens constructed in such a way represent the actual structure of NC metals produced by compaction. By now this method has been well approved by many authors in studying the properties of the NC state in metals ( [50] and the cited publications).…”
Section: Results Of Computer Simulations Of the Diffusion Processes Imentioning
confidence: 95%
“…In one model the annealing twins form at irregularities on GBs where the presence of a packet of stacking faults leads to twin boundary formation [48] and in another model the annealing twins form due to a growth accident on the {111} propagating steps present on migrating GBs so that, during the recrystallization process, twinning is controlled by the existence of stacking faults and the behavior of the migrating boundaries [49]. An MD simulation showed consistencies with the latter model and it was found that in NS FCC metals the annealing twins nucleate and grow from migrating boundaries through the emission of Shockley partial dislocations where the emission sites are mostly near triple junctions and GB ledges [50].…”
Section: The Characteristics Of Annealing and Twin Formationmentioning
confidence: 87%